Design and assembly of plant-based COVID-19 candidate vaccines: reсent development and future prospects - E. A. Uvarova; P. A. Belavin; E. V. Deineko (Вавиловский журнал генетики и селекции)
An outbreak of a new variant of the coronavirus infection, known as COVID-19, occurred at the end of 2019 in China, in the city of Wuhan. It was caused by the SARS-CoV-2 virus. This variant of the virus is characterized by a high degree of variability and, as the current situation with its spread across different regions of the globe shows, it can lead to a progressive spread of infection among the human population and become the cause of a pandemic. The world scientific community is making tremendous efforts to develop means of protection, prevention and treatment of this disease based on modern advances in molecular biology, immunology and vaccinology. This review provides information on the current state of research in the field of vaccine development against COVID-19 with an emphasis on the role of plants in solving this complex problem. Although plants have long been used by mankind as sources of various medicinal substances, in a pandemic, plant expression systems become attractive as biofactories or bioreactors for the production of artificially created protein molecules that include protective antigens against viral infection. The design and creation of such artificial molecules underlies the development of recombinant subunit vaccines aimed at a rapid response against the spread of infections with a high degree of variability. The review presents the state of research covering a period of just over two years, i. e. since the emergence of the new outbreak of coronavirus infection. The authors tried to emphasize the importance of rapid response of research groups from various scientific fields towards the use of existing developments to create means of protection against various pathogens. With two plant expression systems – stable and transient – as examples, the development of work on the creation of recombinant subunit vaccines against COVID-19 in various laboratories and commercial companies is shown. The authors emphasize that plant expression systems have promise for the development of not only protective means under conditions of rapid response (subunit vaccines), but also therapeutic agents in the form of monoclonal antibodies against COVID-19 synthesized in plant cells.